The Analysis of Health and Educational Expenditure as Well as PDRB Per Capita’s Influence on Human Development Index (Study of Cities/Regencies at East Java Province) - Anang Wijayanto (Institute of Research and Community Service, University of Brawijaya)
This research aims to (1) find out what is the effect of educational and health sector expenditure as well as PDRB per capita on Human Development Index of regencies/cities in East Java Province between 2007 and 2012, (2) to find out which dominant variable has a significant impact on Human Development Index of regencies/cities in East Java province between 2007 and 2012. Variables of expenditures of health and educational sectors used ratios of health and education sector expenditures toward total expenditure. Quantitative method was used in this research, using panel data analysis with Fixed Effect Model approach. Estimation result shows that government expenditure on health and educational sectors as well as PDRB per capita has a positive and significant influence, affecting Human Development Index of cities/regencies of East Java Province during the research period. Variable of educational expenditures with its regression coefficient of 0.112 is a variable having the most dominant effect on Human Development Index, compared to that of health expenditure with its regression coefficient of 0.049 and that of PDRB with its regression coefficient of 0.049. Keywords: Human Development Index, health sector expenditure, educational sector expenditure, PDRB per capita.